PSATHYRELLA CANDOLLEANA (FR.:FR.) MAIRE VAR. CANDOLLEANA (FR.) MAIRE: A NEW RECORD OF MUSHROOM FOR NEPAL - Adhikari, M K (Scientific World, 2015)
Recently Psathyrella candolleana (Fr.:Fr.) Maire var. candolleana (Fr.) Maire (1913) was gathered from Lainchour, Kathmandu. It is considered as new record for Nepal. The brief description, distribution and the photograph of the species has been included in this paper. Scientific World, Vol. 12, No. 12, September 2014, page 77-78